Experimental Study on Disposal of Chromium-containing Sludge by Sintering - Shizhe SONG; Zhongcheng LIU; Peijiang LIU; Hongyu HOU; Feng QIAN; Shujuan YU (Kuangchan zonghe liyong)
This is an article in the field of metallurgical engineering. The chromium-containing sludge produced by iron and steel enterprises in the process of steel plate coating is a hazardous waste. It contains a certain amount of iron and calcium oxide, which can be used as a resource through the sintering process. In this paper, chromium-containing sludge was taken as the research object. The application and influence of chromium-containing sludge in sintering were investigated by sintering cup test, and the distribution of chromium element after sintering was studied.The results of sintering pot tests showed that the scheme was feasible.The addition of chromium-containing sludge could promote the formation of complex calcium ferrite phase and improve the performance of sinter. When the ratio of chromium-containing sludge in sintering mixture was less than 2.5%, the yield and utilization coefficient of sinter increased, the drum index also increased, and the return rate and average particle size decreased. During the sintering process, chromium was rarely diffused, and 84～90%, 9%～14% and less than 1% would be fixed in the sinter, return ore, and into the smoke dust, respectively. Overall, the sintering process synergistic treatment of chromium-containing sludge would not produce secondary pollution, which had promising application as an environmental protection strategy for iron and steel enterprises.